Gold ore processing : project development and operations - Adams, Mike D. (Amsterdam : Elsevier Science, 2016)
Gold Ore Processing: Project Development and Operations, Second Edition, brings together all the technical aspects relevant to modern gold ore processing, offering a practical perspective that is vital to the successful and responsible development, operation, and closure of any gold ore processing operation. This completely updated edition features coverage of established, newly implemented, and emerging technologies; updated case studies; and additional topics, including automated mineralogy and geometallurgy, cyanide code compliance, recovery of gold from e-waste, handling of gaseous emissions, mercury and arsenic, emerging non-cyanide leaching systems, hydro re-mining, water management, solid-liquid separation, and treatment of challenging ores such as double refractory carbonaceous sulfides. Outlining best practices in gold processing from a variety of perspectives, Gold Ore Processing: Project Development and Operations is a must-have reference for anyone working in the gold industry, including metallurgists, geologists, chemists, mining engineers, and many others.
Print version record.
Includes bibliographical references and index.
Keywords: Gold ores; Gold mines and mining; TECHNOLOGY & ENGINEERING -- Metallurgy; Gold mines and mining; Gold ores; Electronic books